Digital Literacy and E-Module Integration in Online Learning: A Systematic Literature Review Using PRISMA Framework - yeliza; Mehdi Manoocherzadeh; Hamed Barjesteh (Journal of Sustainable Educational Technology and Innovation, 2026)
Background:Digital transformation has accelerated the adoption of online learning, making digital literacy and e-modules essential for effective learning. However, research trends on their integration remain insufficiently explored.Aims:This study analyzes research trends, intellectual structures, and the role of digital literacy and e-module integration in online learning through bibliometric analysis and a systematic literature review (PRISMA)Methods:A bibliometric analysis and PRISMA-based SLR were conducted using articles from Scopus and Google Scholar. Data were screened, cleaned with OpenRefine, and analyzed using Biblioshiny and VOSviewer to examine publication trends, collaborations, citations, and research themes.Results:Publications increased during 2024-2026, with digital literacy, e-learning, online learning, and e-modules as dominant themes. The findings show that digital literacy improves online learning effectiveness, while e-modules enhance engagement, independent learning, and critical thinking. Artificial intelligence and adaptive learning emerged as promising future research topics.Conclusion:Digital literacy and e-module integration are key factors in improving online learning. This study highlights current research trends, identifies research gaps, and provides recommendations for future technology-enhanced education